Effects of plant age on nitrogen uptake and distribution by greenhouse plants - El-Jaoual, T; Cox, D (Journal of plant nutrition, 1998)
Water-soluble nitrogen (N) fertilizer is intensively used in greenhouse crop production. Any N not used by a crop is subject to leaching as nitrate (NO3- N), which may pollute groundwater. A close correlation between N supply and N uptake by plants would increase the efficiency of N fertilization and minimize the possibility of NO3-N pollution. The objectives of this study were to measure N uptake by American marigold (Tagetes erecta L. 'First Lady') and New Guinea Impatiens (NGI) (Impatiens hawkeri Bull. 'Selenia') during growth, to determine the effect of plant age on N uptake, to determine if the two species have a preference for NO3-N or ammonium (NH4-N), and to determine the total N required for 70 days of growth. The plants were grown in solution culture using solutions supplying 120 mg each of NO3-N and NH4-N. At ten day intervals, six cultures were chosen at random for nutrient solution analysis and plant sampling for dry weight and tissue analysis. Nitrate-N uptake was greater than NH4-N uptake throughout the experiment for both marigold and NGI. Total N uptake by marigold was greater during the first 50 days after transplanting with maximum N uptake during the period 30 to 50 days. In contrast, N uptake by NGI was greater during the period 40 to 70 days after transplanting. Maximum N uptake for NGI occurred during the period 60 to 70 days. Results of this study suggest that early N fertilization of marigold could be more important for their growth and quality than N applied later. For NGI, N fertilization later in the crop's development appears to be more important than early on. The total N absorbed by marigold during the experiment was 1.1 gm N plant-1; for NGI the quantity was 0.5 gm N plant-1